2019
DOI: 10.4274/tjo.galenos.2018.06887
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation Syndrome and Antidepressant Drug Use

Abstract: Objectives:To investigate the relationship between pseudoexfoliation syndrome (PES) and the use of antidepressant medications.Materials and Methods:This population-based, cross-sectional study included 2,017 of 2,356 invited subjects who were randomly selected from the Turkish Statistical Institute database (www.turksat.gov.tr/) as part of an epidemiologic study which specifically aimed to detect the prevalence of PES in the province of Eskişehir. During the examination, a detailed questionnaire was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Literature review of positive risk factors for XFS in general [Tables 5 - 7 ][ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ] and XFS in young subjects [ Table 8 ][ 82 83 84 85 86 87 88 89 90 91 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature review of positive risk factors for XFS in general [Tables 5 - 7 ][ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ] and XFS in young subjects [ Table 8 ][ 82 83 84 85 86 87 88 89 90 91 …”
Section: Resultsmentioning
confidence: 99%
“…In the Lebanese cohort under investigation, XFS was associated with advanced age, glaucoma, habitual ocular rubbing, and longer time for cataract surgery. While advanced age [ Table 6 ],[ 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 ] glaucoma [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] and longer surgery duration[ 100 ] are well established risk factors for XFS [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 <...>…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the patient-specific treatment schemes has gained importance in glaucoma management recently, the vascular parameters are gradually becoming important in terms of diagnosis, progression, and treatment algorithms especially in XFG, which is known to affect the vascular system more and cause increased vascular resistance. [18][19][20][21][22][23][24] Even a comprehensive slit-lamp examination is sufficient to diagnose XFS, and XFG is a clinical diagnosis depends on detection of glaucomatous damage; in particular cases with XFS it is hard to determine whether the VF defect is related with glaucoma or related with other co morbidities. Yarmohammadi et al 25 have found that that OCTA potentially shows promise for identifying focal glaucomatous damage before the first VF defect develops.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Its concomitance with other systemic diseases such as hypertension (HT), cardiovascular disease (CVD), myocardial infarction (MI), peripheral vascular disease, ischemic brain disease (IBD), stroke, neurosensory hearing loss (NSHL), and depression suggests that PEX-S is a part of systemic diseases. [ 13 14 ]…”
mentioning
confidence: 99%